Determining the anisotropy and exchange parameters of polycrystalline spin-1 magnets. (12th September 2019) - Blackmore, W J A; Brambleby, J; Lancaster, T; Clark, S J; Johnson, R D; Singleton, J; Ozarowski, A; Schlueter, J A; Chen, Y-S; Arif, A M; Lapidus, S; Xiao, F; et al.
Abstract: Although low-dimensional S  = 1 antiferromagnets remain of great interest, difficulty in obtaining high-quality single crystals of the newest materials hinders experimental research in this area. Polycrystalline samples are more readily produced, but there are inherent problems in extracting the magnetic properties of anisotropic systems from powder data. Following a discussion of the effect of powder-averaging on various measurement techniques, we present a methodology to overcome this issue using thermodynamic measurements. In particular we focus on whether it is possible to characterise the magnetic properties of polycrystalline, anisotropic samples using readily available laboratory equipment. We test the efficacy of our method using the magnets [Ni(H2 O)2 (3, 5-lutidine)4 ](BF4 )2 and Ni(H2 O)2 (acetate)2 (4-picoline)2, which have negligible exchange interactions, as well as the antiferromagnet [Ni(H2 O)2 (pyrazine)2 ](BF4 )2, and show that we are able to extract the anisotropy parameters in each case. The results obtained from the thermodynamic measurements are checked against electron-spin resonance and neutron diffraction. We also present a density functional method, which incorporates spin–orbit coupling to estimate the size of the anisotropy in [Ni(H2 O)2 (pyrazine)2 ](BF4 )2 .